2014
DOI: 10.1002/ejlt.201400353
|View full text |Cite
|
Sign up to set email alerts
|

A high drying temperature causes degradation of sterols and tocopherols in yellow‐seeded Brassica napus oils

Abstract: The aim of the conducted investigations was to determine the effect of drying temperature on the changes in free fatty acid, phytosterol and tocopherol (T) contents in yellow‐seeded Brassica napus oils. Seeds were dried in a thin layer at 40, 60, 80, 100 and 120°C. Changes in phytosterols were assessed using GC‐MS, while tocopherols were assessed by HPLC. Degradation of phytosterols and tocopherols and an increased content of free fatty acids followed the applied drying temperature. During drying at 40 and 60°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…Gawrysiak-Witulska et al . [15], by researching the effect of drying yellow-seeded rapeseeds, showed in a control sample (of oil from undried seeds) that the free fatty acid content was 1.13 mg KOH/g. Drying at 40 and 60 °C did not result in any statistically significant changes in the free fatty acid content.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gawrysiak-Witulska et al . [15], by researching the effect of drying yellow-seeded rapeseeds, showed in a control sample (of oil from undried seeds) that the free fatty acid content was 1.13 mg KOH/g. Drying at 40 and 60 °C did not result in any statistically significant changes in the free fatty acid content.…”
Section: Resultsmentioning
confidence: 99%
“…Gawrysiak-Witulska et al . [15] studied the changes in tocochromanol in yellow rapeseed during the phases of postharvest processing, taking into account the drying of seeds under different temperature conditions (40, 60, 80, 100, and 120 °C). They showed that the initial tocopherol content of the seeds after collection was 610.5 mg/kg of oil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, research conducted by Goffman and Möllers (2000) demonstrated that PC-8 was degraded more readily than tocopherols during storage of whole rapeseed. PC-8 losses have also been noted during the process of yellow-seeded rapeseed drying (Gawrysiak-Witulska et al, 2015). However, detailed analysis showed that PC-8 losses induced by air-drying at a temperature of 40-60°C were greater than those of total tocopherols; in turn, at 100-120°C drying, the losses were smaller than those found for total tocopherols.…”
Section: Resultsmentioning
confidence: 97%
“…One-year storage of dried seeds at a temperature of 10ºC caused further losses. In investigations concerning drying the seed of the yellow-seeded variety, tocopherol losses were reported to reach 23% in the process of air-drying at 120ºC (Gawrysiak-Witulska et al, 2015). Furthermore, there have been investigations of tocopherol losses caused by improper conditions of rapeseed storage (moisture 10-15.5% and temperature 25-30ºC) (Gawrysiak-Witulska et al, 2011).…”
Section: Introductionmentioning
confidence: 99%